Escrita colaborativa no ensino superior: análise exploratória da interação entre pares no quadro do Interacionismo Sociodiscursivo - Cardoso, Adriana (2018)
This paper focuses on the analysis of peer interaction in a collaborative writing task implemented in higher education. The task involved the production of a scientific paper's ab-stract (just like this one) by students attending the course unit of Portuguese Academic Writ-ing (1st year of the Bachelor’s degree in Basic Education). The study offers an exploratory analysis of one dyad interaction on the basis of the Socio-discursive Interacionism frame-work. In line with Bulea-Bronckart (2014), five different action figures are suggested to ana-lyse the student’s conceptions about the writing production of a scientific paper's abstract, showing how these figures rely on discourse types and other linguistic choices.